Circle RNA circ_0007331 promotes colorectal carcinoma by targeting miR-205-5p/high-mobility group A2 axis. Issue 4 (1st April 2022) - Wang, Lihui; Weng, Weiming; Yang, Shuhui; Yang, Shasha; Du, Richang
ABSTRACT: Colorectal cancer (CRC) is a common malignancy of the gastrointestinal tract. CircRNAs have been reported to play regulatory roles in many cancers, including CRC. This study focuses on the role of circ_0007331 in CRC. Differentially expressed circRNAs in CRC were screened using the GEO database. RT-qPCR was used to analyze mRNA expression. StarBase and TargetScan were used to predict targeting relationships and then verified by the dual luciferase reporter assay along with the RNA pull-down assay. CCK-8 as well and transwell assays were used to measure cell viability, migration, and invasion. Protein levels were determined using western blotting. circ_0007331 is expressed more frequently in patients with CRC. The inhibition of circ_0007331 expression reduced the viability, colony formation, migration, and invasion of CRC cells. However, inhibition of miR-205-5p or elevation of high-mobility group A2 (HMGA2) can reverse the function of inhibited circ_0007331 in tumor cells. This study demonstrated that the circ_0007331/miR-205-5p/HMGA2 axis promotes CRC development. Thus, circ_0007331 may be a potential biomarker for CRC. Graphical Abstract: uf0001